2015
DOI: 10.1371/journal.ppat.1005022
|View full text |Cite
|
Sign up to set email alerts
|

α2-Macroglobulin Can Crosslink Multiple Plasmodium falciparum Erythrocyte Membrane Protein 1 (PfEMP1) Molecules and May Facilitate Adhesion of Parasitized Erythrocytes

Abstract: Rosetting, the adhesion of Plasmodium falciparum-infected erythrocytes to uninfected erythrocytes, involves clonal variants of the parasite protein P. falciparum erythrocyte membrane protein 1 (PfEMP1) and soluble serum factors. While rosetting is a well-known phenotypic marker of parasites associated with severe malaria, the reason for this association remains unclear, as do the molecular details of the interaction between the infected erythrocyte (IE) and the adhering erythrocytes. Here, we identify for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 63 publications
2
73
2
1
Order By: Relevance
“…Thus, it will be important to explore if both rosetting and nonrosetting PfEMP1 variants are contributing to adult SM. Although DC6 binding properties are uncharacterized, recent studies have shown that DBLζ and DBLe mediate binding to IgM and α2-macroglobulin, and it has been hypothesized that binding to these serum factors can cross-link multiple PfEMP1 to increase the binding affinity of N-terminal domains (54,55). Further sequencing of DC6 variants will be necessary to assess whether DC6 and DC8 are part of the same or different proteins in severe isolates, and to determine the binding properties of DBLζ and DBLe Indian domains to serum factors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it will be important to explore if both rosetting and nonrosetting PfEMP1 variants are contributing to adult SM. Although DC6 binding properties are uncharacterized, recent studies have shown that DBLζ and DBLe mediate binding to IgM and α2-macroglobulin, and it has been hypothesized that binding to these serum factors can cross-link multiple PfEMP1 to increase the binding affinity of N-terminal domains (54,55). Further sequencing of DC6 variants will be necessary to assess whether DC6 and DC8 are part of the same or different proteins in severe isolates, and to determine the binding properties of DBLζ and DBLe Indian domains to serum factors.…”
Section: Discussionmentioning
confidence: 99%
“…PECAM1 binding (Treutiger et al , ) has been associated with PfEMP1 containing DC5 (Berger et al , ), but var transcripts encoding DC5 PfEMP1 were not found in high abundance in the studied children. Binding to IgM (Semblat et al , , ; Stevenson et al , ) and alpha‐2‐macroglobulin (Stevenson et al , ) has been mapped to C‐terminal PfEMP1 domains, DBLε and/or DBLζ, which exhibited higher transcript proportions in children with uncomplicated malaria (Fig EV1).…”
Section: Discussionmentioning
confidence: 99%
“…While the role of IgM binding in rosetting remains unclear, it appears to strengthen the bond of the central IE with the surrounding erythrocytes. Stevenson et al (2015) recently reported that the serum protein α 2 -macroglobulin (α 2 M) is able to induce rosetting in vitro and ex vivo, using several parasite isolates. In contrast to IgM, α 2 M elicits rosetting alone, while the presence of IgM significantly lowers the concentration of α 2 M required.…”
Section: Rosetting and Clumping: Consequences For Sequestration Anmentioning
confidence: 99%